GDF15 participates in epithelial cell senescence in radiation-induced lung injury through the ERK1/2-p16 signaling pathway - Jing Liu; Dongyang Lv; Hengjiao Wang; Defu Yang; Ying Xu; Ying Yan (PLoS ONE, 2026)
Objective Radiation-induced lung injury (RILI) is a common complication of thoracic radiotherapy that can compromise treatment outcomes and reduce the quality of life of cancer patients. Cellular senescence is increasingly recognized as an important biological process in the development of RILI. This study aimed to identify senescence-associated molecules involved in RILI and to investigate their potential mechanisms of action. Methods Bioinformatics analysis was performed by integrating differential gene expression profiles from a RILI-related GEO dataset with a senescence-related gene set, which identified growth differentiation factor 15 (GDF15) as a candidate molecule of interest. A rat model of RILI was established, and inflammatory injury and fibrosis were evaluated by hematoxylin and eosin (HE) staining and Masson’s trichrome staining. DNA damage was assessed by γH2AX immunofluorescence. Senescence-associated changes were evaluated by senescence-associated β-galactosidase (SA-β-gal) staining and detection of p53, p21, p16, and GDF15 expression by Western blot. In addition, in vivo and in vitro experiments were performed to further explore the potential mechanism associated with GDF15 in radiation-induced epithelial senescence. Results Bioinformatics analysis identified GDF15 as a prominently upregulated senescence-related gene in RILI. In irradiated rat lungs, γH2AX expression was significantly increased, accompanied by inflammatory infiltration, fibrotic changes, and upregulation of senescence-associated markers. SA-β-gal staining further supported the presence of radiation-induced senescence in vivo. Similar findings were observed in irradiated BEAS-2B cells. Mechanistic experiments showed that GDF15 knockdown attenuated radiation-induced senescence and downregulated the expression of p-ERK1/2 and downstream p16, while ERK1/2 inhibition reduced senescence-associated β-gal staining and p16 expression. These findings suggest that radiation-induced GDF15 may contribute to epithelial cell senescence during RILI, potentially through the ERK1/2-p16 signaling pathway. Conclusion Our findings suggest that GDF15 is upregulated in response to ionizing radiation and may participate in epithelial cell senescence during the development of RILI. This process appears to be associated with the ERK1/2-p16 signaling pathway. These results provide additional insight into the molecular mechanisms underlying RILI and suggest that GDF15 may represent a potential target for future therapeutic intervention.